DISTRIBUTION CHANNELS INFLUENCING SATISFACTION AND LOYALTY ON CREDIT SERVICE ADOPTION OF SMALL AND MEDIUM-SIZED BUSINESS IN THAILAND - Srisornkompon, Palida (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The research on distribution channels that influence satisfaction and loyalty on credit service adoption of small and medium-sized business in Thailand aims to 1. study the level of opinions on distribution channels, satisfaction and loyalty and to 2. study the causal relationship of distribution channel factors influencing satisfaction and loyalty by collecting data from 400 samples of small and medium business entrepreneurs aged 35-45 years. Structural equation analysis, covariance-based SEM, Structural equation analysis of covariance test to find a relationship and the influence of independent variables on dependent variables. The results of the research in Objective 1 found that in terms of online distribution channels, small and medium-sized business operators want banks to provide online services with a convenient, fast and secure connection system in receiving services. On the offline side, the bank provides services with adequate branches and call center connections, and on the online mixed with offline side, services are provided at branches and linked online, ready to provide continuous advice. For satisfaction, entrepreneurs are satisfied with the speed when processing transactions. And loyalty means coming back to ask for more credit limits at the highest level. And the research results in objective 2 found that the distribution channel on the online mixed with offline services has an influence on satisfaction (a positive relationship) and also influences loyalty in using credit services. And all 3 channels also influence loyalty through the central variable of satisfaction. From the results of the study, it is recommended that bank operators focus on creating policies regarding integrated credit service channels in both formats in order to reach consumers seamlessly.